Serine/Arginine-Rich Splicing Factor 3 and Heterogeneous Nuclear Ribonucleoprotein A1 Regulate Alternative RNA Splicing and Gene Expression of Human Papillomavirus 18 through Two Functionally Distinguishable cis Elements - Ajiro, Masahiko; Tang, Shuang; Doorbar, John; Zheng, Zhi-Ming (Journal of virology, 2016)
Human papillomavirus 18 (HPV18) is the second most common oncogenic HPV type associated with cervical, anogenital, and oropharyngeal cancers. Like other oncogenic HPVs, HPV18 encodes two major (one early and one late) polycistronic pre-mRNAs that are regulated by alternative RNA splicing to produce a repertoire of viral transcripts for the expression of individual viral genes. However, RNA cis -regulatory elements and trans -acting factors contributing to HPV18 alternative RNA splicing remain unknown. In this study, an exonic splicing enhancer (ESE) in the nucleotide (nt) 3520 to 3550 region in the HPV18 genome was identified and characterized for promotion of HPV18 929^3434 splicing and E1^E4 production through interaction with SRSF3, a host oncogenic splicing factor differentially expressed in epithelial cells and keratinocytes. Introduction of point mutations in the SRSF3-binding site or knockdown of SRSF3 expression in cells reduces 929^3434 splicing and E1^E4 production but activates other, minor 929^3465 and 929^3506 splicing. Knockdown of SRSF3 expression also enhances the expression of E2 and L1 mRNAs. An exonic splicing silencer (ESS) in the HPV18 nt 612 to 639 region was identified as being inhibitory to the 233^416 splicing of HPV18 E6E7 pre-mRNAs via binding to hnRNP A1, a well-characterized, abundantly and ubiquitously expressed RNA-binding protein. Introduction of point mutations into the hnRNP A1-binding site or knockdown of hnRNP A1 expression promoted 233^416 splicing and reduced E6 expression. These data provide the first evidence that the alternative RNA splicing of HPV18 pre-mRNAs is subject to regulation by viral RNA cis elements and host trans -acting splicing factors. IMPORTANCE Expression of HPV18 genes is regulated by alternative RNA splicing of viral polycistronic pre-mRNAs to produce a repertoire of viral early and late transcripts. RNA cis elements and trans -acting factors contributing to HPV18 alternative RNA splicing have been discovered in this study for the first time. The identified ESS at the E7 open reading frame (ORF) prevents HPV18 233^416 splicing in the E6 ORF through interaction with a host splicing factor, hnRNP A1, and regulates E6 and E7 expression of the early E6E7 polycistronic pre-mRNA. The identified ESE at the E1^E4 ORF promotes HPV18 929^3434 splicing of both viral early and late pre-mRNAs and E1^E4 production through interaction with SRSF3. This study provides important observations on how alternative RNA splicing of HPV18 pre-mRNAs is subject to regulation by viral RNA cis elements and host splicing factors and offers potential therapeutic targets to overcome HPV-related cancer.